Fragmenting globalization the politics of preferential trade liberalization in China and the United States - Zeng, Ka 1973-; Li, Xiaojun 1981- (University of Michigan Press, 2021)
"Global supply chain integration is not only a rapidly growing feature of international trade, it is responsible for fundamentally changing trade policy at international and domestic levels. Ka Zeng and Xiaojun Li argue that global supply chain integration pits firms and industries that are more heavily dependent on foreign supply chains against those that are less dependent on intermediate goods for domestic production. Given that final goods are produced with both domestic and foreign suppliers, businesses whose supply chain will be disrupted as a result of increased trade barriers should lobby for preferential trade liberalization to maintain access to those foreign markets. Moreover, businesses whose products are used in the production of goods in foreign countries should also support preferential trade liberalization to compete with suppliers from other parts of the world. This book uses multiple methods, including cross-sectional, time series analysis of the pattern of Preferential Trade Alliance formation by existing World Trade Organization members; a firm-level survey; and case studies of the pattern of corporate support for regional trade liberalization in both China and the United States. The authors show that the growing fragmentation of global production, trade, and investment is altering trade policy away from the traditional divide between export-oriented and import-competing industries"--
Keywords: International trade; Business logistics / United States; Business logistics / China; Business logistics; China; United States; Electronic books